Occurrence and antimicrobial resistance traits of Escherichia coli from wild birds and rodents in Singapore - Ong, Kar Hui (2021)
Antimicrobial resistance (AMR) in Escherichia coli (E. coli) poses a public health concern worldwide. Wild birds and rodents, due to their mobility, are potential vehicles for transmission of AMR bacteria to humans. Ninety-six wild birds’ faecal samples and 135 rodents’ droppings samples were collected and analysed in 2017. Forty-six E. coli isolates from wild birds and rodents were subjected to AMR phenotypic and genotypic characterisation. The proportion of E. coli isolates resistant to at least one of the antimicrobials tested from wild birds (80.8%) was significantly higher than that of isolates from rodents (40.0%). The proportion of E. coli isolates resistant to each antimicrobial class for wild birds was 3.8% to 73.1% and that for rodents was 5.0% to 35.0%. Six out of 26 E. coli isolates from wild birds (23.1%) and two out of 20 (10.0%) isolates from rodents were multi-drug resistant (MDR) strains. These MDR E. coli isolates were detected with various antimicrobial resistance genes such as blaTEM-1B and qnrS1 and could be considered as part of the environmental resistome. Findings in this study suggested that wild birds and rodents could play a role in disseminating antimicrobial resistant E. coli, and this underscores the necessity of environment management and close monitoring on AMR bacteria in wild birds and rodents to prevent spreading of resistant organisms to other wildlife animals and humans.